(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the therapeutic effectiveness of combining the Tam dieu hoan herbal formula with therapeutic ultrasound and electrical stimulation in the treatment of knee osteoarthritis. Subject and methods: A controlled clinical interventional study was conducted on 60 patients with knee osteoarthritis. The study group (n = 30) received a combination of Tam dieu hoan herbal formula, therapeutic ultrasound, and electrical stimulation, while the control group (n = 30) was treated according to the standard treatment regimen. Treatment outcomes were compared before and after a 15-day intervention period. Results: After 15 days of treatment, the study group showed significantly greater improvement than the control group. The VAS score decreased by 4.7 ± 0.8 points in the study group compared with 3.2 ± 0.7 points in the control group (p < 0.05). Synovial fluid thickness and synovial membrane thickness were markedly reduced, with better outcomes in the study group (p < 0.05). The total WOMAC score decreased by 26.2 ± 5.6 points, exceeding the reduction observed in the control group (20.1 ± 5.3 points). Knee flexion range increased by 21.5 ± 4.1 degrees, which was significantly greater than that in the control group (12.8 ± 3.7 degrees) (p < 0.05). Conclusion: The combination of Tam dieu hoan with therapeutic ultrasound and electrical stimulation was more effective than the standard treatment alone in managing knee osteoarthritis, resulting in significant pain relief, reduction of inflammation and joint effusion, and improved knee function.